Legal protection of geological heritage - Luneva, Elena V. (Journal of the Belarusian State University. Law, 2022)
The protection and rational use of the geological heritage of international importance is carried out within the framework of the functioning of the UNESCO global geoparks. Scientific sources show many ways of integrating geopark regulations into national legislation. At the CIS level, the importance of preserving rare geological objects, creating and developing geoparks, as well as the need for legal protection of the abiotic component of the natural environment as a whole (geological outcrops, objects and complexes of inanimate nature, mountainous areas, etc.) is recognised. However, in the Republic of Belarus, in the legal protection of nature, the bias is made in favour of the conservation of biological or species and landscape diversity. Belarusian legislation does not use the terms «geodiversity», «geological heritage», «geopark». At the end of the article, general recommendations on the possible development of the legislation of the Republic of Belarus on the protection of geological heritage are formulated.